Unsolved problems in stellar physics : a conference in honor of douglas gough - Stancliffe, Richard J.; Dewi, Jasinta; Houdek, Gunter; Martin, Rebecca G.; Tout, Christopher A. (Melville, NY : American Institute of Physics, 2007)
26